A fully coupled damage-plasticity model for unsaturated geomaterials accounting for the ductile–brittle transition in drying clayey soils. (August 2016) - Le Pense, Solenn; Arson, Chloé; Pouya, Amade
Highlights: We developed a constitutive model coupling damage, plasticity and suction. Model reproduces experimental features, such as swelling, brittle and ductile behaviours. Framework flexibility enables refining independent components of the model. Graphical abstract: Abstract: This paper presents a hydro-mechanical constitutive model for clayey soils accounting for damage-plasticity couplings. Specific features of unsaturated clays such as confining pressure and suction effects on elastic domain and plastic strains are accounted for. A double effective stress incorporating both the effect of suction and damage is defined based on thermodynamical considerations, which results in a unique stress variable being thermodynamically conjugated to elastic strain. Coupling between damage and plasticity phenomena is achieved by following the principle of strain equivalence and incorporating the double effective stress into plasticity equations. Two distinct criteria are defined for damage and plasticity, which can be activated either independently or simultaneously. Their formulation in terms of effective stress and suction allows them to evolve in the total stress space with suction and damage changes. This leads to a direct coupling between damage and plasticity and allows the model to capture the ductile/brittle behaviour transition occurring when clays are drying. Model predictions are compared with experimental data on Boom Clay, and the flexibility of the model is illustrated by presenting results of simulations in which either damage or plasticity dominates the coupled behaviour.